Simultaneous application of refractance window and microwave drying: A novel hybrid technique for fruit dehydration to reducing drying time and improve bioactive compound retention - C. Ramírez; H. Núñez; R. Vallejos; K. Belmonte; S. Almonacid; F Marra (Future Foods, 2025)
Refractance window (RW™) and microwave (MW) are two drying technologies characterized by short drying time and high-quality retention. This study investigated the effect of drying apple slices (as a model food), using a novel system: RW™ assisted with microwaves (RW-MW). Drying time, moisture content, water activity (aw), total polyphenol content, antioxidant capacity and color change were determined. The study also aimed to model the drying process through Fick’s second law and anomalous diffusion model based on fractional calculus. Drying was performed with RW™, and RW-MW using two power densities: 815 W/kg and 1165 W/kg. RW™ and RW-MW were set at 98 °C. In both cases, the drying process was performed until the apple slices reached a moisture content lower than 0.097 g of water/ g sample (wet basis) and aw below 0.4. Bioactive compound retention was assessed by measuring total polyphenol content (TPC), and antioxidant capacity (AC). The results showed that applying microwave power densities of 815 W/kg and 1165 W/kg simultaneously during RW™ drying allowed reduced drying time by up to 66 % compared to RW™ alone, maintaining the retention of TPC and AC. This study demonstrated that RW-MW is a technology that allows for reduced drying times while maintaining high bioactive compound retention compared to RW™ drying.